Delayed Cerebral Vasculopathy Following Cranial Radiation Therapy for Pediatric Tumors - Wang, Chenyang; Roberts, Kenneth B.; Bindra, Ranjit S.; Chiang, Veronica L.; Yu, James B. (Pediatric neurology, 2014)
Radiation-induced cerebrovascular injury is a well-known phenomenon. We analyze reported cases of delayed radiation-induced cerebrovasculopathy that present as moyamoya syndrome and/or intracerebral hemorrhage and to statistically analyze the relationship between radiation dose and the interval period between radiation and the presentation of cerebrovasculopathy. Patients ages <21 years at the time of radiation were included in analysis. A review of previous publications yielded 77 cases of delayed radiation-induced cerebrovasculopathy consisting of 45 cases of moyamoya syndrome, 30 cases of intracerebral hemorrhage, and two cases of both. The median age at radiation was 4.8 years, with a range of 0.5-20 years. Approximately, 75% of these patients received radiation at the age of <9 years. The median interval period for moyamoya cases was 3.3 years (range: 0.3-20; P < 0.001), whereas the median interval period from radiation to presentation for intracerebral hemorrhage cases was 7.5 years (range: 0.8-27). There was significant association between radiation dose and interval from radiation to moyamoya syndrome (P < 0.001), whereas for patients with intracerebral hemorrhage, the association was insignificant (P = 0.31). Pediatric patients who presented with moyamoya generally presented earlier than those who presented with intracerebral hemorrhage, suggesting that moyamoya may be a factor that predisposes the patient to intracerebral hemorrhage. In patients who presented with moyamoya, there was a statistically significant correlation between increasing doses of radiation and shorter time from radiation to disease presentation.